Government Healthcare Spending and Cancer Mortality: A Statistical Analysis Over 15 Years in 18 Countries (Journal of Innovative Research, 2025)
This study examines healthcare spending in 18 countries in Asia, Europe and the Americas from 2001 to 2015 and finds notable variations in cancer mortality. Gender-specific effects were demonstrated by significantly lower mortality-to-incidence ratios in countries with more investment, particularly among women. Interestingly, despite more spending, male mortality remained higher, exposing unrecognized inequalities in healthcare consumption. This work reveals the critical relationships between public investment, policy efficacy, and cancer outcomes. This study offers policymakers helpful recommendations on how to enhance health outcomes and eliminate disparities in cancer treatment worldwide.